Green Bioanalytical and Pharmaceutical Analysis of Voriconazole and Tadalafil by HPLC - Dogan, Aysegul; E. Basci, Nursabah (Current Pharmaceutical Analysis, 2017)
Objective: Green pharmaceutical and bioanalytical methods for Voriconazole and Tadalafil were developed and validated using an environment friendly organic modifier without any extraction step. Replacing toxic solvent in bioanalytical HPLC is the first greening approach in chromatographic drug analysis in plasma. Method: Analytical C18 columns and mobile phases containing conventional solvents or propylene carbonate with/without ethanol and/or buffer were used in optimization study. Results: Optimized chromatographic conditions were Shim-Pack XR-ODS (100 × 2.0 mm, 2.2 µm) column and the mobile phase consisted of propylene carbonate/(70% phosphate buffer (50 mM, pH=3.0) + 30% ethanol) (10:90, v/v). Limit of detection and limit of quantification in tablet analysis were respectively 0.1 µg mL-1 and 0.5 µg mL-1 for both Voriconazole and Tadalafil. Lower limit of quantification in plasma analysis was found to be 0.005 µg mL-1 for both analyte. Conclusion: Green HPLC methods presented here were accurate, precise, specific, sensitive, rugged, robust, reliable in long-term use and successfully applied to pharmaceutical and plasma analysis.
Keywords: voriconazole